231k views
2 votes
Let f(x) = -3x + 7 and g(x) = 2x^2 - 8, (g×f)(x)

2 Answers

2 votes

Answer:Let f(x) = 2x – 1, g(x) = 3x, and h(x) = x2 + 1. Compute the following.

1. f(g(-1)) 2. f o h(3) 3. g(f(-5))

4. h(f(x)) 5. f(f(x)) 6. h o g(x)

II. Let f(x) = 9 – x , g(x) = x2 + 4, and h(x) = x – 2. Compute the following:

7. g(f(12)) 8. f(g(2)) 9. h(f(x))

III.

User Arthur Gevorkyan
by
5.4k points
1 vote

The function multiplication results to

(g * f)(x) = 6x³ + 14x² - 24x - 56

How to find the (g * f)(x)

To find (g * f)(x), you need to multiply the functions g(x) and f(x). 4

(g * f)(x) = g(x) * f(x)

Given that:

f(x) = -3x + 7 and

g(x) = 2x² - 8:

(g * f)(x) = (2x² - 8) * (3x + 7)

(g * f)(x) = 6x³ + 14x² - 24x - 56

User Scrubmx
by
5.4k points